2014
DOI: 10.1016/j.molcel.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Oxidation Maintains the TCA Cycle and Cell Survival during Impaired Mitochondrial Pyruvate Transport

Abstract: Summary Alternative modes of metabolism enable cells to resist metabolic stress. Inhibiting these compensatory pathways may produce synthetic lethality. We previously demonstrated that glucose deprivation stimulated a pathway in which acetyl-CoA was formed from glutamine downstream of glutamate dehydrogenase (GDH). Here we show that import of pyruvate into the mitochondria suppresses GDH and glutamine-dependent acetyl-CoA formation. Inhibiting the mitochondrial pyruvate carrier (MPC) activates GDH and re-route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
467
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(535 citation statements)
references
References 48 publications
38
467
6
3
Order By: Relevance
“…Increased oxidative glutaminolysis and reductive carboxylation upon MPC inhibition were observed in transformed cell lines, although the relative contributions of these fates of glutamine were dependent on the cell line and growth conditions (59,60). Glutamine anaplerosis supports cellular proliferation in transformed cells and inhibition of glutaminase-or glutamate dehydrogenase-sensitized cells to growth inhibition upon treatment with UK-5099 (60). Analogous to the differences in glutamine metabolism observed in primary and transformed cultured cells, glutamine seems to play a more significant anaplerotic role in the brain than in the fetal liver, as glutamine was the second most downregulated metabolite in the Mpc1 KI/KI brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxidative glutaminolysis and reductive carboxylation upon MPC inhibition were observed in transformed cell lines, although the relative contributions of these fates of glutamine were dependent on the cell line and growth conditions (59,60). Glutamine anaplerosis supports cellular proliferation in transformed cells and inhibition of glutaminase-or glutamate dehydrogenase-sensitized cells to growth inhibition upon treatment with UK-5099 (60). Analogous to the differences in glutamine metabolism observed in primary and transformed cultured cells, glutamine seems to play a more significant anaplerotic role in the brain than in the fetal liver, as glutamine was the second most downregulated metabolite in the Mpc1 KI/KI brain.…”
Section: Discussionmentioning
confidence: 99%
“…We found that alanine provides a robust anaplerotic substrate in several cellular models of MPC deficiency, as well as in vivo in embryonic brain and liver. It has been demonstrated that Mpc2-deficient mitochondria exhibit no alterations in alanine uptake (62), and decreased steady-state alanine concentrations have been observed in several MPC-deficient cell models and in vivo (59,60,62). The decrease in steadystate alanine has been interpreted as a result of most cellular alanine being derived from mitochondrial pyruvate, but we sought to test the flux of alanine itself.…”
Section: Discussionmentioning
confidence: 99%
“…Specific chemical inhibition of pyruvate transport into the mitochondrion synergizes with inhibition of glutaminolysis to cause increased death 250 .…”
Section: Oncogenic Change Role In Glutamine Metabolismmentioning
confidence: 99%
“…Pyruvate might be used as the beginning of the TCA cycle and as a raw material of free amino acid. [25] Acetylpropionic acid was not detected either, which was reported to be absence from brewed soy sauce, and was considered a judgement factor for Japanesestyle fermented soy sauce. [26] These organic acids influence the acidity of soy sauces and ensure a balance in taste.…”
Section: Organic Acid In Commercial Soy Saucementioning
confidence: 99%